2002
DOI: 10.1103/physreva.66.063201
|View full text |Cite
|
Sign up to set email alerts
|

Emission of singly and doubly charged light fragments fromC60r+(r=4

Abstract: Asymmetrical fission of C 60 rϩ (rϭ4 -9) ions are studied in Xe 25ϩ -C 60 collisions at 100 keV impact energy (vϷ0.18 a.u.). The branching ratios for the emission of a singly or a doubly charged light fragment, C m ϩ or C m 2ϩ , are measured for each initial charge state r. The measured m-dependent branching ratios for the singly charged C m ϩ fragment emission channels are reproduced using a simple statistical model. The ionization energies I(C 60Ϫ2n qϩ ) for even numbered fullerenes C 60Ϫ2n qϩ (qϭ1 -5, 8; nϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the case of anthracene and pyrene molecules, it is found that the pericondensed form (pyrene) is more stable in kilo-electron volt ion-PAH collisions. To shed further light on the intriguing stability issues of (multiply) ionized PAHs, multicoincidence experiments similar to the ones for ion-fullerene collision [37,38,41,51] and high-level calculations of fission barriers [42] are needed. Further model developments in which the actual PAH molecular structures are taken into account would be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of anthracene and pyrene molecules, it is found that the pericondensed form (pyrene) is more stable in kilo-electron volt ion-PAH collisions. To shed further light on the intriguing stability issues of (multiply) ionized PAHs, multicoincidence experiments similar to the ones for ion-fullerene collision [37,38,41,51] and high-level calculations of fission barriers [42] are needed. Further model developments in which the actual PAH molecular structures are taken into account would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Recent high-level calculations show that pyrene and coronene are thermodynamically unstable for charge states exceeding 3 and 4, respectively [36]. However, as in the case of C 60 fullerenes [37][38][39][40][41][42], fission barriers should prevent even more highly charged species from prompt decay. The present experiments show that C 16 expected for C 24 H 5+ 12 a small feature is present.…”
Section: B Multiply Charged Molecular Cationsmentioning
confidence: 99%
“…In our previous works, delayed asymmetric fission processes have been observed for C 4þ 60 and C 5þ 60 recoil ions [14,30]. Concerning evaporation processes, since our experimental set-up does not allow the detection of neutral fragments, it had not been possible to determine the lifetimes associated to these processes by analyzing coincidence spectra between fragments.…”
Section: Delayed Evaporation Of C 3þ 60mentioning
confidence: 93%
“…Andersen et al [28] have shown for C À 60 that when the internal energy is lower than 40 eV the cooling rate is greater than the dissociation rate. In our case, we have estimated the decay rates fission processes for C rþ 60 (r = 4-6) with the Arrhenius formula [29] in which the fission barriers have been set according to [30]. The calculated rates are displayed as a function of the excitation energy in Fig.…”
Section: µS Moveable Common Stopmentioning
confidence: 99%
“…Recently a number of the experimental data were published on the ionization and fragmentation of C 60 fullerenes under the ion bombardment. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] According to the experimental data, the C 2 evaporation is known as a preferential mechanism in the fragmentation of a fullerene, which accompanies the electron excitation and/or the plasmon excitation. The electron excitation (or, emission) by a charged particle is closely related to the electronic stopping power, while the phonon excitation is due to the nuclear stopping power.…”
Section: Introductionmentioning
confidence: 97%